Mobile Technology Usage in Education Process: Natural Science Teacher Standpoint - V. Lamanauskas; V. Šlekienė (University of Sofia, 2021)
New smart mobile technologies are being implemented in schools. Tablet computers, mobile telephones and other devices are used in education process. However, it has not been unambiguously revealed what influence mobile technology usage has on education achievement and learning motivation. Therefore, it is purposeful to explore mobile technology (MT) usage peculiarities in education process: phenomena limiting and encouraging the usage, teachers' opinion regarding MT usage and application perspectives. On the other hand, one of the aims of national education policy is to make conditions for education participants to skilfully use technologies in education, and encourage them to create new ICT devices. Teachers' role is the leading in MT usage, in order the technologies constantly accompanying the student become reliable helpers in learning. Reliable scientific knowledge is necessary concerning this question. Pilot research was carried out during October-December months 2019, in which 120 (n=19, 16% male, n=101, 84% female) Lithuanian natural science teachers from various general education schools took part. During the research, it was sought to analyse the frequency of MT usage, application limiting factors, and school maintenance from the point of view of teachers. It was ascertained that schools were provided with MT at a rather different level, and their usage frequency was also different. The main application hindrance in education process is insufficient provision of schools with mobile devices, and the available equipment being old and of poor quality. The management of educa-tion process, teacher and student MT application skill shortage and lack of time for the improvement of these skills are also considered hindrances. MT usage consequence, efficacy, and effectiveness in education process problematic analysis, including also MT integration into educational practice is considered an especially important perspective of the further research studies.